Introducing blockchain with Lisp : implement and extend blockchains with the Racket language - Sitnikovski, Boro (Apress, 2021)
Implement blockchain from scratch covering all the details with Racket, a general-purpose Lisp. You'll start by exploring what a blockchain is, so you have a solid foundation for the rest of the book. You'll then be ready to learn Racket before starting on your blockchain implementation. Once you have a working blockchain, you'll move onto extending it. The book's appendices provide supporting resources to help you in your blockchain projects. The recommended approach for the book is to follow along and write the code as it's being explained instead of reading passively. This way you will get the most out of it. All of the source code is available for free download from GitHub. You will: Discover the Racket programming language and how to use it Implement a blockchain from scratch using Lisp Implement smart contracts and peer-to-peer support Learn how to use macros to employ more general abstractions.